Meta-analysis of RNA-Seq datasets allows a better understanding of P. tricornutum cellular biology, a requirement to improve the production of Biologics - Isabelle Boulogne; Charlotte Toustou; Muriel Bardor (Scientific Reports)
Abstract The marine diatom Phaeodactylum tricornutum is currently used for various industrial applications, including the pharmaceutical industry as a cost-effective cell biofactory to produce Biologics. Recent studies demonstrated that P. tricornutum can produce functional monoclonal antibodies, such application is currently limited by the production yield that hinders industrialization. Therefore, it is necessary to understand and control the cell biology of P. tricornutum to improve the Biologics production yield. Transcriptomic analyses have recently been used by the pharmaceutical industry to improve the production of Biologics in mammalian cells, especially Biologics titer and cell productivity. Hence, in the present work, we performed a meta-analysis of seven publicly available RNA-Seq datasets from different strains of P. tricornutum, for which the culture conditions were chosen as similar as possible. We analyzed the differential expression of genes that are involved in biological processes that are well known to potentially impact the bioproduction and critical quality attributes of Biologics. Therefore, the expression of genes involved in the N-glycan biosynthesis, protein export and secretion, protein quality control and proteasome, as well as those encoding proteases were analyzed and compared. The results pave the way towards optimizing Biologics production in P. tricornutum and highlight that the Pt4, Pt3 Ov and Pt8 strains seem to be the most promising P. tricornutum strains.